If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + n) = 9 + n (1 * 3 + n * 3) = 9 + n (3 + 3n) = 9 + n Solving 3 + 3n = 9 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 3 + 3n + -1n = 9 + n + -1n Combine like terms: 3n + -1n = 2n 3 + 2n = 9 + n + -1n Combine like terms: n + -1n = 0 3 + 2n = 9 + 0 3 + 2n = 9 Add '-3' to each side of the equation. 3 + -3 + 2n = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 2n = 9 + -3 2n = 9 + -3 Combine like terms: 9 + -3 = 6 2n = 6 Divide each side by '2'. n = 3 Simplifying n = 3
| -4y-2=9y-3 | | 7=3+6 | | 4-20(-8)= | | 0.20x+6=14 | | 10=25-5T-T^2 | | 6a-5=-3a | | 7/2x-3x=-1/2x+3/2+5/2x | | 0=-16t^2+240t | | 7m=9m+36 | | 20*-8= | | 25x^2-44=-8 | | -6z-12=20 | | 8n-11=5n+19 | | 6x+3(3x+30)=-60 | | 0.045x+0.006(5000-x)=247.50 | | 0.5x+6=14 | | 60x-.2x^2=0 | | 0=2x^2-6x | | 0.045+0.006(5000-x)=247.50 | | -7x+2(4x-11)=-31 | | 10x+6=5x-9 | | N-39=14-4n | | y=14x+8b | | (2*17.50)+x=78 | | N-3n=14-2n | | y=14x+8x | | 4x+5/-3=7 | | 7x+12=5x-8 | | 0.5x+5=13 | | r^2-8r=-14 | | 3x-2=124 | | 7.1/44.2 |